Tertiary lymphoid structure patterns aid in identification of tumor microenvironment infiltration and selection of therapeutic agents in bladder cancer - An, Ye; Sun, Jian-Xuan; Xu, Meng-Yao; Xu, Jin-Zhou; Ma, Si-Yang; Liu, Chen-Qian; Liu, Zheng; Wang, Shao-Gang; Xia, Qi-Dong (Frontiers in Immunology, 2022)
Background: Tertiary lymphoid structures (TLSs) are emerging as a potential predictor of prognosis and response to immunotherapy in some solid tumors. However, the comprehensive role of TLSs in bladder cancer remains unclear. Methods: Eighteen bladder cancer (BCa) datasets were downloaded from The Cancer Genome Atlas (TCGA), Gene Expression Omnibus (GEO), ArratyExpress and IMvigor210. Based on 39 validated TLS signature genes (TSGs), we evaluated the TLS patterns in all patients, and correlated the TLS patterns with prognosis and tumor microenvironment (TME) cell-infiltrating characteristics. The cox regression model and principal component analysis (PCA) algorithms were used to construct the TLS score, which helps to quantify the TLS pattern in individuals. Results: The landscape of 39 validated TSGs in BCa was assessed first. Five distinct TLS patterns and four gene clusters were determined. TLS cluster C2 and gene cluster A were thought to be characterized by mature TLSs and showed better prognosis and higher immune cells infiltration than other clusters. The TLS score was discovered to be tightly correlated with the infiltration level of immune cells, and could predict the maturation status of TLSs to some extent. We found TLS score was an excellent predictor for prognosis in patients with BCa independent of tumor mutation burden (TMB), and low TLS score was related to better prognosis than high TLS score. Besides, low TLS score was correlated with a better response to immune checkpoint blockade (ICB) immunotherapy and commonly used chemotherapy drugs. Conclusions: Our work demonstrated the characteristics of TLSs in BCa. By using the TLS score, we could evaluate the TLS pattern in individuals. Better understanding of TLS pattern and the usage of TLS score could help instruct clinical strategy and precision medicine for BCa.